Prevalence of self-medication practice among health sciences students in Kermanshah, Iran - Alireza Abdi; Azam Faraji; Fateme Dehghan; Alireza Khatony (BMC, 2018)
Abstract Background The possibility of self-medication is higher in health sciences students than other students because of easy access to drug information resources and relatively sufficient familiarity with various kinds of drugs. The current study was aimed to determine the prevalence of self-medication and its related factors among the health sciences students. Methods A total of 250 health sciences students were included in this cross-sectional study via random sampling. Data were collected by a researcher-made self-medication questionnaire. The collected data were analyzed by SPSS-20 software using descriptive and inferential statistics (chi-square test). Results The prevalence of self-medication was 89.6%. Prior experience about the illness, non-seriousness of the illness and availability of drugs were the most prevalent reasons for self-medication. The most commonly used medications included common cold drugs, analgesics and antibiotics. The most frequently used medications were cold pill, acetaminophen pill and amoxicillin capsule. Most students obtained their pharmaceutical information from the pharmacist physician and online sources. Self-medication did not show a significant difference in terms of variables such as age, gender, marital status, insurance status and residence. Conclusion Given the high prevalence of self-medication among the health sciences students, training courses about the self-medication risks, more supervision over prohibition of over-the-counter drugs and adequate facilities for students' access to medical services are suggested to be provided.